Virtual Reality for Digital Transformation in the Business Era: A Systematic Review - Ruiz Rodriguez, Fabry Cesar Antonio; Iparraguirre Huaranga, Aaron Edu; Rada Mota, Luis Carmelo (LACCEI, 2025)
This systematic literature review (SLR) aims to analyze real-life use cases, adoption barriers, and critical success factors, providing a comprehensive view of the role of virtual reality (VR) as a driver of technological innovation and digital transformation in the corporate world. The methodology used integrates the PICOC method, which allowed for the formulation of research questions and the development of a general search equation in Scopus. Likewise, the PRISMA protocol was applied to select, using inclusion and exclusion criteria, 71 original articles that answered the PICOC questions. In this sense, the results show VR applications in sectors such as education, healthcare, industry, and culture, highlighting benefits such as improved learning, risk reduction, process optimization, and personalization of the user experience. Barriers such as high initial costs, lack of standards, and accessibility and inclusion challenges are also identified. It is concluded that VR has transformative potential when integrated with emerging technologies, underscoring the need for inclusive, collaborative, and adaptive strategies to drive effective and sustainable digital transformation in diverse organizational environments.